Insights into the role of reactive sulfhydryl groups of Carbonic Anhydrase III and VII during oxidative damage. (1st January 2017) - Monti, Daria M.; De Simone, Giuseppina; Langella, Emma; Supuran, Claudiu T.; Di Fiore, Anna; Monti, Simona M.
Abstract: Carbonic anhydrases (CAs) III and VII are two cytosolic isoforms of the α-CA family which catalyze the physiological reaction of carbon dioxide hydration to bicarbonate and proton. Despite these two enzymes share a 49% sequence identity and present a very similar three-dimensional structure, they show profound differences when comparing the specific activity for CO2 hydration reaction, with CA VII being much more active than CA III. Recently, CA III and CA VII have been proposed to play a new role as scavenger enzymes in cells where oxidative damage occurs. Here, we will examine functional and structural features of these two isoforms giving insights into their newly proposed protective role against oxidative stress.